TEKTONIK DAERAH MUARA TEBO PROPINSI JAMBI - -, Iyan Haryanto; -, Ismawan; -, Faisal Helmi; -, Edy Sunardi; -, Oeke Sobarin; Indah Putri, Yunita Rossa (Bulletin of Scientific Contribution, 2008)
Geological structure of Muara Tebo area was influenced by subduction between Eurasian and India-Australian Plates. Regional tectonic of this area dominantly yield an amount of fault structure with orientation Northwest-Southeast.Structural pattern of study area dominated by dextral strike-slip and thrust fault, with orientation Northwest-Southeast. The dextral strike-slip fault represent the first structure formed (Early Tertiary) which influenced by transtensional stress. Further, on Neogene Tectonic period the structures influenced by tranversional stress system which affecting inversion. This late tectonic yield an amount of thrust fault.